Composition of Giants 1° North of the Galactic Center: Detailed Abundance Trends for 21 Elements Observed with IGRINS - Govind Nandakumar; Nils Ryde; Gregory Mace; Kyle F. Kaplan; Niels Nieuwmunster; Daniel Jaffe; R. Michael Rich; Mathias Schultheis; Oscar Agertz; Eric Andersson; Christopher Sneden; Emily Strickland; et al. (The Astrophysical Journal, 2024)
We report the first high-resolution, detailed abundances of 21 elements for giants in the Galactic bulge/bar within 1° of the Galactic plane, where high extinction has rendered such studies challenging. Our high-signal-to-noise-ratio and high-resolution, near-infrared spectra of seven M giants in the inner bulge, located at ( l , b ) = (0°, +1°), are observed using the IGRINS spectrograph. We report the first multichemical study of the inner Galactic bulge by investigating, relative to a robust new solar neighborhood sample, the abundance trends of 21 elements, including the relatively difficult to study heavy elements. The elements studied are: F, Mg, Si, S, Ca, Na, Al, K, Sc, Ti, V, Cr, Mn, Co, Ni, Cu, Zn, Y, Ce, Nd, and Yb. We investigate bulge membership of all seven stars using distances and orbital simulations, and we find that the most metal-poor star may be a halo interloper. Our investigation also shows that the inner bulge as close as 1° north of the Galactic Center displays a similarity to the inner disk sequence, following the high-[ α /Fe] envelope of the solar vicinity metal-rich population, though no firm conclusions for a different enrichment history are evident from this sample. We find a small fraction of metal-poor stars ([Fe/H] > −0.5), but most of our stars are mainly of supersolar metallicity. Fluorine is found to be enhanced at high metallicity compared to the solar neighborhood, but confirmation with a larger sample is required. We will apply this approach to explore the populations of the nuclear stellar disk and the nuclear star cluster.